Program to Enhance Adjustment to Residential Living (PEARL): Effect on Adjustment, Anxiety, Quality of Life, and Stress. Issue 5 (20th October 2022) - Davison, Tanya E.; McCabe, Marita P.; Busija, Ljoudmila; Graham, Annette
ABSTRACT: Objectives: The Program to Enhance Adjustment to Residential Living (PEARL) is a five session intervention primarily designed to address high rates of depression in newly admitted residents. This study reports the efficacy of PEARL on secondary outcomes of resident adjustment, symptoms of anxiety, quality of life, and stress. Methods: A cluster randomized controlled trial was conducted with 219 newly admitted nursing home residents (M age = 85.5 years) from 42 nursing homes. Outcomes were assessed at baseline, post-intervention, and at two and six month post-intervention follow-up, compared to a standard care condition. Results: There was a significant overall condition by time interaction for adjustment ( p = .027) and quality of life ( p = .015), but not for stress ( p = .309). While the overall condition by time interaction was not significant for anxiety ( p = .221), there was a significant interaction contrast six-month post-intervention, indicating a greater decrease in anxiety scores in the intervention group relative to control ( p = .039). Conclusions: This study demonstrates the broad effects of PEARL on the wellbeing of newly admitted residents. Clinical Implications: PEARL is a brief intervention that may be feasible for routine use in nursing homes to facilitate adjustment and improve residents' quality of life.